2023
DOI: 10.1177/09645284231202811
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into weight loss: acupuncture combined with a very low-carbohydrate diet—a Swiss experience

Massimo Fumagalli,
Raymond G Landgraaf,
Nadège N Schiavi-Lods
et al.

Abstract: Objective: The objective of this study was to assess the effects of an acupuncture–diet program for treatment of overweight and obesity. Methods: The program consisted of weekly acupuncture sessions combined with a very low-carbohydrate diet in patients with a body mass index (BMI) of 25 kg/m2 or above. Data were collected retrospectively between 2002 and 2021 in seven clinics in Switzerland through automated data extraction of existing medical records. The treatments described are standard care at the facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the few studies in adults, sex distribution differs between studies, ranging from women only ( 49 ) to two-thirds of the population subgroups being women ( 53 , 198 , 199 ). Recent studies reported that changes in the gut microbiota associated to metabolic illnesses are different in men and women ( 201 ) and this could be translated to acupuncture treatment ( 50 ). To the best of our knowledge, no studies analysing acupuncture in combination with gut microbiota analysis in children have been performed to date.…”
Section: Acupuncture Clinical Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the few studies in adults, sex distribution differs between studies, ranging from women only ( 49 ) to two-thirds of the population subgroups being women ( 53 , 198 , 199 ). Recent studies reported that changes in the gut microbiota associated to metabolic illnesses are different in men and women ( 201 ) and this could be translated to acupuncture treatment ( 50 ). To the best of our knowledge, no studies analysing acupuncture in combination with gut microbiota analysis in children have been performed to date.…”
Section: Acupuncture Clinical Human Studiesmentioning
confidence: 99%
“…A synergetic effect between lifestyle modifications and acupuncture is therefore suggested and this combined intervention may be a more effective and viable option. Recently, a large-scale retrospective chart review was performed of 11,233 obese patients with combined acupuncture and VLCD underscored that the combination can induce weight reduction in obese patients ( 50 ). However, due to the lack of a control group, a prospective trial is needed to validate these findings and therefore such RCT is currently executed.…”
Section: Acupuncture Clinical Human Studiesmentioning
confidence: 99%